(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
This article analyzes the pragmatic functions of paralinguistic means in Uzbek communicative culture. The role of non-linguistic means such as facial expressions, gestures, body movements, tone and pauses in the communication process, their functions such as enhancing meaning, clarifying, expressing attitude and giving emotional coloring are highlighted on the basis of discourse examples. The results of the study show that paralinguistic signs in Uzbek communicative culture appear as a means that complement the content and sometimes have an independent communicative value